Pelatihan Aplikasi Software Matematis dalam Pembelajaran Matematika - Retno Marsitin; Nyamik Rahayu Sesanti; Djoko Adi Susilo (Universitas Pahlawan Tuanku Tambusai, 2022)
The rapid development of technology requires mathematics teachers to master mathematical software applications. However, some mathematics teachers have not mastered technology in mathematics learning, especially mathematical software applications. The solution to this problem is organizing community service activities through mathematical software application training in mathematics learning. The community service activity uses training modules that provide detailed and complete explanations and examples presented excitingly, so the participants are not bored. A series of community service activities include materials delivery, training and mentoring, discussion, and evaluations. Mathematics teachers were actively involved during the activities to the end and evaluation. This community service activity aims to improve the quality of mathematics teachers in utilizing mathematical software applications in mathematics learning. The responses to the training activities were very positive, so it can be concluded that the training activities were carried out well and the achievements in accordance with the goals and targets specified.